The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.34220/issn.2222-7962/2020.2/17
|View full text |Cite
|
Sign up to set email alerts
|

Rational Use of Fumed and Natural Oak Wood

Abstract: Fumed oak wood is valuable and one of the most environmentally friendly natural materials. As a result of a long stay of wood in flowing river water and in contact with bottom soil without air access, an individual process of staining of each trunk occurs. It consists in changing the chemical composition of the wood. The wood acquires increased strength and a beautiful color scheme. It is established that the degree of coloring of fumed oak wood depends on the amount of iron oxides in it (Fe2O3). There are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
1
0
3
Order By: Relevance
“…The study of physical and mechanical characteristics of bog oak at the age of 100-150 years has shown that these indicators completely coincide with those previously described [15][16][17]. Therefore, the main attention was paid to the physical and mechanical properties of bog oak with an age of 2500-3000 years.…”
Section: Figuresupporting
confidence: 72%
See 1 more Smart Citation
“…The study of physical and mechanical characteristics of bog oak at the age of 100-150 years has shown that these indicators completely coincide with those previously described [15][16][17]. Therefore, the main attention was paid to the physical and mechanical properties of bog oak with an age of 2500-3000 years.…”
Section: Figuresupporting
confidence: 72%
“…It should be noted that shrinkage in bog oak (at the age of 2500-3000 years) in both directions is less than in natural one. And shrinkage in bog oak at the age of 100-150 years is much more according to [16,17].…”
Section: Figurementioning
confidence: 99%
“…В ВГЛТУ выполнены исследования на древесине сосны, произрастающей в сухих борах лесостепной зоны России, после повреждения сильным низовым и беглым верховым пожаром [2][3][4]. В результате длительного мониторинга установлено, что у древесины в насаждениях, расположенных в сухих борах лесостепной зоны, после повреждения пожаром происходит снижение прочностных свойств гораздо быстрее, чем у древесины в насаждениях, произрастающих во влажных борах севера европейской части России.…”
Section: деревопереработка химические технологииunclassified
“…-С. 127-157 [1,4]. После указанного срока стояния на корню происходит существенное снижение прочностных показателей древесины.…”
Section: деревопереработка химические технологииunclassified
See 1 more Smart Citation